Digital Therapeutics (DTx) for Temporomandibular Disorder (TMD) - Park, Sang-Yoon; Kim, Daehyun; Kim, Bong-Ju; Ju, Kyung Won; Kim, Young-Kyun; Park, Joo-Young; Lee, Jong-Ho (Archives of Clinical and Medical Case Reports, 2022)
Due to the pandemic situation of the Covid-19 virus, our daily life has changed a lot [1]. Many changes have also taken place in the fields of medicine and dentistry. The most prominent field is the field of digital medicine, and the field of digital therapeutics (DTx) has developed rapidly along with the technology of other fields [2,3]. In the case of digital therapeutics, it is evaluated that it can be remarkably applied in the field that requires behavioral control or the field that requires the approach of mental health medicine. In addition, studies are being carried out notably in high blood pressure, diabetes, heart-related diseases, addiction, dementia, and Attention Deficit/Hyperactivity Disorder (ADHD) that require management as a chronic disease. However, in the field of dentistry, there are not many fields where digital therapeutics are applied prominently, but application to temporomandibular disorder can be devised,4 and the reason for this can be discussed in this article.